NEO MODERNISME ISLAM INDONESIA: WACANA KEISLAMAN DAN KEBANGSAAN NURCHOLISH MADJID - Suryani Suryani (JWP (Jurnal Wacana Politik), 2016)
Neo modernism emerged as a critical discourse face the phenomenon of modernist Islamic thought that emphasizes reason and ratio in view of the existence of religion in a struggle and debate ideas discourse on Islam and society. In the neo modernism discourse, the phenomenon of religious exclusivity becomes a very important study. Exclusive theology is used by some hard-line Islamic groups to judge other religions or other Islamic groups that are not inline with Islam that they believe to be the real truth. Neo modernism evolved to respons this religious exclusivity and the religious inclusivity comes to make a new discourse on Islam which has the main idea of an understanding of the universal message delivered by God not only to one particular religion but also to other religions in the scriptures each. The efforts to avoid subjectivity of religion and promote objectivity in the social sphere in Nurcholish Madjid’s thought will not reduce the religious existence, but will make it more effective and elegant can also be easily accepted by modern society without suspicion.